2000
DOI: 10.1021/jf0005871
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Method for Analysis of Secoisolariciresinol Diglucoside in Flaxseeds

Abstract: A method was developed for the analysis of secoisolariciresinol diglucoside (SDG) in flaxseeds. The analytical method involves extraction of defatted flaxseed flour with dioxane/ethanol, aqueous base-hydrolysis, solid-phase purification of an SDG-containing fraction, and quantitative analysis by high-performance liquid chromatography (HPLC). Pure SDG was isolated from flaxseed using different column chromatographic methods and used, as external standard, for the calibration of the method and for quantification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(131 citation statements)
references
References 15 publications
2
127
1
Order By: Relevance
“…The content of secoisolariciresinol diglucoside in flaxseed has been reported to vary from 6.1 to 25.9 mg g (1 (Johnsson et al 2000;Eliasson et al 2003). Lignans are classified as phytoestrogens because of their structural similarities with natural and synthetic estrogens and antiestrogens, but they are also able to compete with endogenous estradiol for estrogen receptors.…”
Section: Flaxseed Compositionmentioning
confidence: 99%
“…The content of secoisolariciresinol diglucoside in flaxseed has been reported to vary from 6.1 to 25.9 mg g (1 (Johnsson et al 2000;Eliasson et al 2003). Lignans are classified as phytoestrogens because of their structural similarities with natural and synthetic estrogens and antiestrogens, but they are also able to compete with endogenous estradiol for estrogen receptors.…”
Section: Flaxseed Compositionmentioning
confidence: 99%
“…Yuan et al (2008) found SDG in DFF in the range of 6-29 mg g −1 and Li et al (2008) reported a SDG content of 15.4 mg g −1 in flaxseed. In addition, Johnsson et al (2000) obtained SDG in the range of 11.7-24.1 mg g −1 in DFF and 6.1-13.3 mg g −1 in whole flaxseed from cultivars of Denmark and Sweden. Hao and Beta (2012) reported that the SDG content in flaxseed hulls varied from 16.4 to 33.9 mg g −1 .…”
Section: Sdg Content In Flaxseed Cultivarsmentioning
confidence: 94%
“…DFF was prepared by the Soxhlet method for 2 h at 70°C with nhexane, as described by Johnsson et al (2000) with some modifications. DFF (5 g) was mixed with 100 mL of 0.1 mmol L −1 sodium methoxide and sonicated for 30 min.…”
Section: Purification Of Sdg Sdg Extractionmentioning
confidence: 99%
See 2 more Smart Citations